Potret Feminisme dalam Cerpen “Jangan Pulang Jika Kamu Perempuan” Karya Riyana Rizki Yuliatin - Pipit Aprilia Susanti; Sartika Samad (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted with the aim of looking at the forms of injustice experienced by women based on marginalization, stereotypes, and violence experienced by the main character in the short story "Don't Go Home If You're a Woman" by Riyana Rizki Yuliatin. The research method used is descriptive qualitative method. The results of the study show that 1) female characters experience stereotypes as girls who live in villages that uphold customs, the choice to go home after being rushed in the merariq tradition is considered a disgrace that not only embarrasses herself but also the woman's family and even the village. 2) The main character also gets marginal treatment from fellow women who live in the village. By making the main character a bad example for girls who are not optimal when doing housework. 3) The main character also received verbal violence not only from his own family but also from residents around the village.